2012
DOI: 10.1029/2012gl052910
|View full text |Cite
|
Sign up to set email alerts
|

Robust future precipitation declines in CMIP5 largely reflect the poleward expansion of model subtropical dry zones

Abstract: [1] Robust subtropical precipitation declines have been a prominent feature of general circulation model (GCM) responses to future greenhouse warming. Recent work by the authors showed that for the models making up the Coupled Model Intercomparison Project phase 3 (CMIP3), this drying was found mainly in the midlatitude-driven precipitation poleward of the model subtropical precipitation minima. Here, using more comprehensive diagnostics, we extend that work to 36 new CMIP5 models, and find that CMIP5 robust p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
114
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 22 publications
(46 reference statements)
13
114
1
1
Order By: Relevance
“…Finally, we have shown that the leading pattern of uncertainty in the trends of the mean meridional circulation is able to explain most of the leading pattern of uncertainty in the trends of the hydrological (P 2 E) cycle, in the tropics and the extratropics, and in both seasons. A similar strong linkage between projected changes in precipitation and changes in the atmospheric circulation has recently been reported by Scheff and Frierson (2012).…”
Section: Discussionsupporting
confidence: 82%
“…Finally, we have shown that the leading pattern of uncertainty in the trends of the mean meridional circulation is able to explain most of the leading pattern of uncertainty in the trends of the hydrological (P 2 E) cycle, in the tropics and the extratropics, and in both seasons. A similar strong linkage between projected changes in precipitation and changes in the atmospheric circulation has recently been reported by Scheff and Frierson (2012).…”
Section: Discussionsupporting
confidence: 82%
“…A strong negative correlation was identified between ECS and the mean May through August RH of the middle and upper troposphere in winter hemisphere subtropics in the CMIP3 models. It was reasoned that the processes drying the troposphere served as an indicator of the interaction between moisture and the tropical circulation and that a connection to future projections existed via the expansion of such dry zones with warming (e.g., [33]) and an associated reduction of clouds. A connection between ECS and the intensities of shallow and deep components of the Hadley circulation was also found.…”
Section: Cloud-related Ecsmentioning
confidence: 99%
“…To the first order, these trends result from the EÀP forcing increase in positive EÀP regions as expected by the Clausius Clapeyron relationship in a warming world [Held and Soden, 2006;Seager et al, 2010]. Recent model studies further suggest that not only the amplitude but also the location of the maximum EÀP forcing may change in the future climate in response to global warming [Seager et al, 2010;Scheff and Frierson, 2012]. It is thus crucial to monitor SSS changes in these cores in order to better understand their relationship to climate change.…”
Section: Introductionmentioning
confidence: 99%